Heterogeneity of Cortical Lesions in Multiple Sclerosis: An MRI Perfusion Study. Issue 3 (March 2013) - Peruzzo, Denis; Castellaro, Marco; Calabrese, Massimiliano; Veronese, Elisa; Rinaldi, Francesca; Bernardi, Valentina; Favaretto, Alice; Gallo, Paolo; Bertoldo, Alessandra
In this study, dynamic susceptibility contrast-magnetic resonance imaging (DSC-MRI) was used to quantify the cerebral blood flow (CBF), the cerebral blood volume (CBV), and the mean transit time (MTT) and to analyze the changes in cerebral perfusion associated with the cortical lesions in 44 patients with relapsing-remitting multiple sclerosis. The cortical lesions showed a statistically significant reduction in CBF and CBV compared with the normal-appearing gray matter, whereas there were no significant changes in the MTT. The reduced perfusion suggests a reduction of metabolism because of the loss of cortical neurons. A small population of outliers showing an increased CBF and/or CBV has also been detected. The presence of hyperperfused outliers may imply that perfusion could evolve during inflammation. These findings show that perfusion is altered in cortical lesions and that DSC-MRI can be a useful tool to investigate more deeply the evolution of cortical lesions in multiple sclerosis.